2021
DOI: 10.51264/inajl.v2i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Irradiance Optimation for Growing Spirulina fusiformis: Biomass, Phycocyanin, and Protein Production

Abstract: The optimization of cyanobacterium microalgae cultivation technology to provide the need for food or feedstocks has recently attracted many investigators. An optimum operation on microalgae cultivation is important to reduce the excessive workload on the aquatic environment. Therefore, this study describes how the varied irradiance (2000 lux, 4000 lux, 6000 lux, 8000 lux, and 10,000 lux) treatments on a bubble column photobioreactor system affected biomass production, phycocyanin, and protein from cyanobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…It has been shown that the paranet application can effectively diminish and even eliminate heat accumulation problems related to extremely high natural solar irradiance, such as a 50% shading level at 31.85 cm diameter column size and a 70% shading level at 12.74 cm diameter column size. This finding is consistent with a previous report that showed higher photosynthetic activity of an A. platensis outdoor culture with 25% irradiance shading [35] Some reports have emphasized heat accumulation as a major problem in closed photobioreactor systems, particularly in outdoor applications, while using cooling systems to overcome the problem will require significant investment and operational costs [25]. This study reveals a possible way to overcome this problem by means of paranet shading and its combination with the column size.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It has been shown that the paranet application can effectively diminish and even eliminate heat accumulation problems related to extremely high natural solar irradiance, such as a 50% shading level at 31.85 cm diameter column size and a 70% shading level at 12.74 cm diameter column size. This finding is consistent with a previous report that showed higher photosynthetic activity of an A. platensis outdoor culture with 25% irradiance shading [35] Some reports have emphasized heat accumulation as a major problem in closed photobioreactor systems, particularly in outdoor applications, while using cooling systems to overcome the problem will require significant investment and operational costs [25]. This study reveals a possible way to overcome this problem by means of paranet shading and its combination with the column size.…”
Section: Discussionsupporting
confidence: 92%
“…Satya et also observed a trend of an in-line increase in chlorophyll and phycocyanin content with the protein synthesis in Spirulina fusiformis culture, although the increasing trend that was observed with rising light intensity up to 10,000 lux (~81.9 W/m 2 ) is in contrast with the observation in this experiment. This contrast observation is possibly due to different light availability and can be explained in terms of a light response curve model, as the light range up to 10,000 lux (~81.9 W/m 2 ) in a laboratory culture is below the saturated point for the algal physiology [25], while in this outdoor experiment the average daily irradiance range was considerably higher, up to more than 25,000 lux (~204.9 W/m 2 ) (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated aquaculture is a technology that has been widely applied by small household industries in freshwater environments, especially in Asia [14]. Such as the research conducted in Research Center for Limnology, Indonesia Institute of Sciences that showed an improvement in pond production efficiency by providing an additional natural feed of minute duckweed Lemna perpusilla biomass that grown in self generated media obtained from the fish cultivation system [14,15,16].…”
Section: Figure 1 Spirodela Polyrhiza (Mass and Single Appearance)mentioning
confidence: 99%